Implementation of Decency Test and Strategic Position Feasibility in accordance with Law Number 5 of 2014 in Medan City Government, Deli Serdang Regency and Samosir Regency - Robinson Sembiring; Muba Simanihuruk (Universitas Medan Area, 2020)
This study seeks (1) to explore local government strategies in selecting personnel for strategic positions; (2) studying the role of the RPA (Regional Personnel Agency) in carrying out the Decency and Appropriateness Test of personnel applying for the